CHALLENGES OF FEMALE ENTREPRENEURSHIP: a survey with women entrepreneurs - Pedezzi, Bruna; Rodrigues, Lilian Segnini (Revista Interface Tecnológica, 2020)
This paper aims to analyze how women entrepreneurs deal with their families, the problems and professional demands of the market and what difficulties they face in this process, also differentiating between those who are not mothers and those who are. To this end, a questionnaire was applied to women entrepreneurs in the city of São Carlos and region. It is based on the hypothesis that it is fully possible for women to be a mother and, at the same time, to deal with their personal life, their family and the challenges inherent to their business, however, the effort that she will have to make for this is very big . The questionnaire was sent online to women entrepreneurs and obtained 35 responses. It is concluded that the challenges that these women face are great and one of them is the fact that they have to reconcile all family demands with the professionals. The previously raised hypothesis was confirmed.
Keywords: Entrepreneurial women; Female entrepreneurship; Entrepreneurial mothers